Manajemen Program Adiwiyata dalam Meningkatkan Karakter Peduli Lingkungan - Saipul Annur; Tutut Handayani; Ikhwan Sidik (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to 1) describe the management of the Adiwiyata program at the Al-Furqon Integrated Islamic Elementary School Palembang, 2) describe the improvement of the environmental care character of the students of the Al-Furqon Integrated Islamic Elementary School Palembang. This research is a qualitative research. The informants in this study were the Principal, Deputy Principal for Curriculum, Head of the Adiwiyata Team, teachers and students. Methods of data collection by observation, interviews and documentation. Test the validity of the data using triangulation techniques and sources. Data analysis uses an interactive model that starts from data collection, data reduction, data presentation and conclusions. The results showed that: 1) The management of the Adiwiyata program at SDIT Al-Furqon Palembang has been implemented well. The planning function is carried out by setting goals, formulating current conditions, identifying conveniences and obstacles, and developing plans. The organizing function is carried out by referring to plans and goals, determining the main tasks, dividing tasks to individuals, and allocating resources. The implementation function is carried out by implementing the four Adiwiyata components, namely environmentally friendly policies, environmentally friendly curriculum, participatory-based environmental activities and management of environmentally friendly supporting facilities. The supervisory function is carried out by setting standards, comparing implementation with standards and determining deviations and taking corrective actions. 2) Increasing the character of environmental care in students at SDIT Al-FurqonPalembang is seen through the attitude of students in preventing environmental damage, as well as repairing natural damage.